2019
DOI: 10.1111/ijpo.12595
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of overweight among youth with chronic conditions in the United States: An update from the 2016 National Survey of Children's Health

Abstract: Summary Background Surveillance of overweight trends among youth with chronic conditions can inform the prioritization of funding, research and intervention. Objectives The primary objective of this study was to utilize the 2016 National Survey of Children's Health (NSCH) data to provide current estimates of the prevalence of overweight among US youth with common chronic conditions. A secondary purpose was to examine parental concern about weight status among youth with chronic conditions who were overweight. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…Our findings are consistent with most of the pooled Health Behavior in School‐aged Children scores representing 15 European countries, which reported that after adjusting for age and socioeconomic status, males with disabilities spent significantly longer times in recreational ST behaviors compared to those without disabilities 14 . These results seem to be in agreement with other authors who found that a high proportion of adolescents living with visual or hearing impairments do not meet ST recommendations, and this prevalence seems to increase over time 15 . This is an important issue with possible clinical relevance since adolescents with disabilities are at risk of developing further health conditions due to their sedentary behavior 16 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are consistent with most of the pooled Health Behavior in School‐aged Children scores representing 15 European countries, which reported that after adjusting for age and socioeconomic status, males with disabilities spent significantly longer times in recreational ST behaviors compared to those without disabilities 14 . These results seem to be in agreement with other authors who found that a high proportion of adolescents living with visual or hearing impairments do not meet ST recommendations, and this prevalence seems to increase over time 15 . This is an important issue with possible clinical relevance since adolescents with disabilities are at risk of developing further health conditions due to their sedentary behavior 16 …”
Section: Discussionsupporting
confidence: 92%
“…The ENSE involved a sample of approximately 88,629 schoolchildren from 1,190 educational institutions located in 298 municipalities, and it was estimated through stratified probabilistic, clustered, stratified, and multistage sampling. In the last analysis, in the final sample, 35,404 adolescents (aged [13][14][15][16][17] were included in our study. Further information about the selection of the study sample is shown in Figure S1.…”
Section: Design and Participantsmentioning
confidence: 99%
“…This study focused on 24 405 youth (aged 10-17 years): 13 408 without a chronic condition and 10 997 children with 1 of 19 chronic condition diagnoses included in the NSCH, which included (1) attention-deficit disorder or attention-deficit/ hyperactivity disorder (ADD/ADHD), (2) anxiety problems, (3) arthritis, (4) asthma, (5) autism, (6) behavior or conduct problems, (7) cerebral palsy, (8) cystic fibrosis, (9) depression, (10) developmental delay, (11) diabetes, (12) Down syndrome, (13) epilepsy, (14) frequent or severe headaches, (15) hearing impairments (including deafness), (16) intellectual disability, (17) learning disability, (18) speech disorder, and (19) VIs (including blindness). Participants were identified as those whose parents reported that they had been told by a healthcare professional that their child has the condition and that the child currently has the condition.…”
Section: Samplementioning
confidence: 99%
“…4 While research examining the prevalence of meeting multiple health behavior guidelines among children is increasing, 13,14 and national health initiatives such as Healthy People 2020 outline specific objectives for meeting PA, SB, and SD guidelines, 15 the extension of this integrated framework to the study of health behaviors among youth with chronic conditions is scarce. Yet, a focus on this group is imperative as children with various chronic conditions have been demonstrated to be at greater risk of negative health outcomes, such as overweight 16,17 and having poorer health-related quality of life. 18 To address this scarcity, researchers have begun to examine the prevalence of adherence to PA, ST, and SD guidelines among children with autism spectrum disorder (ASD) 19 and children with visual impairments (VIs).…”
mentioning
confidence: 99%
“…These ancillary data will ultimately allow us to consider the association of these medical conditions and treatments with respect to anthropometric status relative to these novel curves. Another unique opportunity this large cohort provides is to examine secular trends in weight in the US general population since there has been a clear trend of increasing body weight over the last several decades [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%